Agbor Tänzer im Mbari Artists and Writers Club in Ibadan (Of Art Worlds - Collecting and Archiving Modern and Contemporary Art on the African Continent)
Copyright jointly or exclusively held by Iwalewahaus, CBCIU and/or Georgina Beier Estate Executor. CBCIU and Iwalewahaus identifiers currently unavailable.
Keywords: Africa; Dance; Ritual; Artists; Ika (African people); The Mbari Club; Ibadan; Nigeria; Ritual Dance; Cultural Centre